IMPROVEMENT OF QUALIMETRIC QUALITY SELF-ASSESSMENT PERTAINING TO TRAINING OF SPECIALISTS FOR NUCLEAR POWER STATIONS - A. V. Veremko; K. N. Malovik (Наука и техника)
The paper considers problems pertaining to quality self-assessment of educational services at higher education institutions. A qualimetric approach for control and selection of significant quality indicators for educational disciplines has been proposed in the paper.